COMPARISON OF RAINFALL DATA MANAGEMENT BETWEEN INDONESIA AND JAPAN - Intan Supraba (Simposium II UNIID 2017, 2017)
President Joko Widodo administration has launched infrastructure megaprojects development in Indonesia such as build of 3,733 kilometers of new toll roads, 49 dams, bridges, and mega power plant projects with a total capacity of 35,000 megawatts. Civil construction requires rainfall data to design road drainage channel, to calculate reservoir water level fluctuations, to determine the distance between the bottom of the bridge and the water surface, to simulate flood, and to manage water resources. As rainfall data has an important role in infrastructure development, this study aims to compare the rainfall data quality and the ease of access to get that data based on case study between Japan and Indonesia by doing literature review. Results showed that in Japan, hourly rainfall data can be easily and freely accessed from Water Information System website provided by Ministry of Land, Infrastructure, Transportation, and Tourism. Flood warning also can be simply accessed in Japan Meteorological Agency website. In Indonesia, hourly rainfall data is not available in the website, thus users need to submit an official request for obtaining the data. Comprehensiveness of data is questionable. Thus, data management including adding observatory facilities should be improved to support acceleration of infrastructure development in Indonesia.